Towards evidence-based and inclusive models of peer support for long covid: A hermeneutic systematic review. (March 2023) - Mullard, Jordan C.R.; Kawalek, Jessica; Parkin, Amy; Rayner, Clare; Mir, Ghazala; Sivan, Manoj; Greenhalgh, Trisha
Abstract: Since the first wave of COVID-19 in March 2020 the number of people living with post-COVID syndrome has risen rapidly at global pace, however, questions still remain as to whether there is a hidden cohort of sufferers not accessing mainstream clinics. This group are likely to be constituted by already marginalised people at the sharp end of existing health inequalities and not accessing formal clinics. The challenge of supporting such patients includes the question of how best to organise and facilitate different forms of support. As such, we aim to examine whether peer support is a potential option for hidden or hardly reached populations of long COVID sufferers with a specific focus on the UK, though not exclusively. Through a systematic hermeneutic literature review of peer support in other conditions (57 papers), we evaluate the global potential of peer support for the ongoing needs of people living with long COVID. Through our analysis, we highlight three key peer support perspectives in healthcare reflecting particular theoretical perspectives, goals, and understandings of what is 'good health', we call these: biomedical (disease control/management), relational (intersubjective mutual support) and socio-political (advocacy, campaigning & social context). Additionally, we identify three broad models for delivering peer support: service-led, community-based and social media. Attention to power relations, social and cultural capital, and a co-design approach are key when developing peer support services for disadvantaged and underserved groups. Models from other long-term conditions suggest that peer support for long COVID can and should go beyond biomedical goals and harness the power of relational support and collective advocacy. This may be particularly important when seeking to reduce health inequalities and improve access for a potentially hidden cohort of sufferers. Highlights: Co-produced peer support can help people living with Long COVID. Increasing the use of effective peer support may reduce health inequalities. Inclusive peer support can benefit 'hardly reached' Long Covid cohorts. Linking biomedical, relational and socio-political styles are most effective.